Economic and clinical benefits of endometrial radiofrequency ablation compared with other ablation techniques in women with menorrhagia: a retrospective analysis with German health claims data - Bischoff-Everding C; Soeder R; Neukirch B (Dove Medical Press, 2016)
Christoph Bischoff-Everding,1 Ruediger Soeder,2 Benno Neukirch3 1HGC GesundheitsConsult GmbH, Duesseldorf, Germany; 2Gynecological Joint Practice, Mainz, Germany; 3Faculty of Health Care, Hochschule Niederrhein – University of Applied Sciences, Krefeld, Germany Objective: To evaluate the economic and clinical benefits of endometrial radiofrequency ablation (RFA) compared with other ablation techniques for the treatment of menorrhagia.Methods: Using German health claims data, women meeting defined inclusion criteria for the intervention group (RFA) were selected. A comparable control group (other endometrial ablations) was established using propensity score matching. These two groups were compared during the quarter of treatment (QoT) and a follow-up of 2 years for the following outcomes: costs during QoT and during follow-up, repeated menorrhagia diagnoses during follow-up and necessary retreatments during follow-up. Results: After performing propensity score matching, 50 cases could be allocated to the intervention group, while 38 were identified as control cases. Patients in the RFA group had 5% fewer repeat menorrhagia diagnoses (40% vs 45%; not significant) and 5% fewer treatments associated with recurrent menorrhagia (6% vs 11%; not significant) than cases in the control group. During the QoT, the RFA group incurred €578 additional costs (€2,068 vs €1,490; ns). However, during follow-up, the control group incurred €1,254 additional costs (€4,561 vs €5,815; ns), with medication, outpatient physician consultations, and hospitals costs being the main cost drivers. However, none of the results were statistically significant. Conclusion: Although RFA was more cost-intensive in the QoT compared with other endometrial ablation techniques, an average total savings of €676 was generated during the follow-up period. While having evidence that RFA is clinically equivalent to other endometrial ablation procedures, we generated indications that RFA is non-inferior and favorable with regard to economic outcomes. Keywords: menorrhagia, radiofrequency ablation, endometrial ablation, costs, Germany, health claims data